Compiling Supplementary Book for Children with Special Needs Using Communicative Approach To originate Speaking Skills: Compiling Supplementary Book for Children with Special Needs Using Communicative Approach To originate Speaking Skills - kasmudi (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2019)
The reference book givesthe students desirable cultural aspects such as experience, information and facts.The problem statements in this research are:1. How to compile supplement book for children with special needs using communicative approach to grow speaking. 2. To know up to what extent the effectiveness of the Supplement Book for children with special needs with a communicative approach affect s the growth of speaking skills.The objectives of this study are to: 1.To know the compilation of the book supplement for children with special needs to cultivate speaking skills. 2.To know up to what extent the effectiveness of the Supplement Book for children with special needs with a communicative approach affects the growth of speaking skills.This research is done in Research and Development method with Borg and Gall model as cited in Sugiyono. The instruments used in the research are: 1. Observation .2. Interview 3. Questionnaire 4. Test (pre-test and post-test). The population of the research is 5th graderds with special needs while the sample is students with special needs of that class as many as 7 pupils of the odd semester of academic year 2017/2018. The results of this study are: 1. The supplement book for children with special needs with communicative approach to cultivate speaking skills. 2. The book is provenly effective based on pretest and post test undergone.